Meteorological Risks in Doha 2019 Athletics World Championships: Health Considerations From Organizers - Bermon, Stéphane; Adami, Paolo Emilio (Frontiers in Sports and Active Living, 2019)
• The Doha 2019 IAAF World Championships represent a challenge for athletes, workforce and spectators who could compete, work or attend under extreme meteorological conditions. • This short article summarizes the methodology used by the IAAF and the Local Organising Committee to analyse and reduce risks, while complying as much as possible with existing recommendations or policies. • The main steps to be completed are identification and description of weather-related risks, description and whenever possible testing of their possible mitigation measures during test events, revision of these risks once mitigation implemented, and finally drafting a contingency plan for remaining exceptional and impactful occurrences. • Such risk management methodology could apply to other sports, ideally from the host city selection to the delivery of the event.